How emotions can influence customers' Decision Making Process via Social Media? - Umraliyeva, D.; Ayazbay, O.; Yesbergenova, B.; Skidanova, A. (International School of Economics KAZGUU, Nur-Sultan, 2022)
Nowadays, the consumption of social media has become the most popular online activity that people are engaged in. Facebook, Instagram, Twitter and many other apps play a big role in the lives of people around the world. Moreover, social media platforms have become a marketing tool for businesses. It is mainly used for product promotion, to inform customers about up-to-date sales or changes related to the product or service. In other words, social networks are a great tool for interaction and communication between the business and its customers. However, one of the main driven factors that businesses benefit from social media platforms is based on the customer’s emotions. Emotions are a broad concept of the mood, behavior or tone of customers. In the industry of the new generation of social networks, where such persons as influencers are also a phenomenon, consumers listen to their emotions and feelings, due to which there is a faster decision-making process. In the new generation industry of the social media platforms, where popular people known as influencers are also a phenomenon. Therefore, the consumer decision-making process is being speeded up due to being emotionally followed by the feelings of those influencers. The purpose of the thesis is to study the emotions of the clients on social networks and to understand how consumer behavior depends on one’s emotions. To find out how emotions affect customer behavior to avoid any negative consequences for the businesses and get an effective return from the actions of the business. Customer emotions are explained as their mood, that is, their attitude to viewing ads, buying a product and interacting with businesses in any way that involves the decision-making process. Mainly, to study how businesses affect people by using influencers and emotional ads as a marketing tool. High-quality work has been done in order to find out the relationship between consumer behavior and their emotions. This study uses a mixed-method: a quantitative and a qualitative method in order to answer the research questions. The data were collected by a questionnaire with both open and closed questions to study the impact of marketing tools on consumer behavior. The interviewees were both male and female buyers of different ages to ensure the accuracy of the research data.
Keywords: Social Media, emotions, customer decision making process